Factors Affecting and Outcome of Radioactive Iodine Therapy in Hyperthyroidism: A study at Institute of Nuclear Medicine & Allied Sciences (INMAS), Sylhet - Nahar, Kamrun; Akhter, Papia (Bangladesh Journal of Nuclear Medicine, 2018)
Objective: Radioactive iodine therapy (RIT) is the most commonly used modality to treat hyperthyroidism and is indeed in most cases, the treatment of choice. The aim of this study was to assess the clinical outcome one year after radioactive Iodine-131 (RAI -131) therapy and to identify the factors associated with response of the therapy. Patients and Methods: A total 107 hyperthyroid patients were included in this study. All patients were pre-treated with anti-thyroid drugs (ATD). A fixed dose of 8 mCi of radioiodine was given to the patients with Graves’ disease, 12 mCi to patients with single toxic adenoma and 15 mCi to patients with toxic multi-nodular goiter . The patients were done serum FT4 initially and followed up with serum T3, T4, and TSH at three months , six months and one year of RAI therapy . The clinically and biochemically euthyroid and hypothyroid patients were considered as cure of the disease. Results : The cure rate was about 94.7% seen in female patients and 93.8% in male ( P=0.92), 93.6% in younger age group (below 40 years) and 95.0% of the older patients ( P=1.51), 95.5% of the patients who were taking ATD for more than one year and 92.7% of the patients who were taking ATD for less than one year before therapy( P=1.95), 95.4 % of the patients who had initial FT4 level less than 35 pmol/L and 92.7 % of the patients who had high initial FT4 ( P=1.54). Cure rate of Graves’ disease was 45/53 (92.5%), multi-nodular goiter 41/43 (95.3% ) and for single toxic adenoma was 11/11 (100% ) (P= 0.65). The incidence of radioiodine induced hypothyroidism was 6.5 % at three months, 13.1 % at six months and 15.0 % at one year. Overall incidence of cure rate of RAI therapy after one year was 101 (94.4 %). Conclusion: No statistically significant difference was found in the cure rate when sex, age, duration of pretreatment with antithyroid drug, initial FT4 level and cause of hyperthyroidism were considered. From this study it can be concluded that cure rate of RAI therapy is quite good and the pretreatment factors have little influence on the final outcome. Bangladesh J. Nuclear Med. 19(1): 19-23, January 2016